2014
DOI: 10.1080/17439884.2014.942666
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing education to adolescent biology: ‘let teens sleep, start school later’

Abstract: Arne Duncan, US Secretary of State for Education, tweeted in 2013: 'let teens sleep, start school later'. This paper examines early starts and their negative consequences in the light of key research in the last 30 years in sleep medicine and circadian neuroscience. An overview of the circadian timing system in adolescence leading to changes in sleep patterns is given and underpins the conclusion that altering education times can both improve learning and reduce health risks. Further research is considered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 68 publications
2
54
0
2
Order By: Relevance
“…The choice of changing the alarm time from 7:00 h to 8:00 h was motivated by proposed changes in the UK: typical school start-times for adolescents are currently 8:30 h to 9:00 h and a shift to 9:30 to 10:00 h has been mooted32. This follows an extensive and on-going debate in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of changing the alarm time from 7:00 h to 8:00 h was motivated by proposed changes in the UK: typical school start-times for adolescents are currently 8:30 h to 9:00 h and a shift to 9:30 to 10:00 h has been mooted32. This follows an extensive and on-going debate in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding human performance and its relation to sleep is critical to productivity [16], learning [26], and avoiding accidents [16,20]. Human performance is not constant but exhibits daily variations [43].…”
Section: Resultsmentioning
confidence: 99%
“…Maintaining optimal cognitive performance has been found to be important in learning [26], productivity [16], and avoiding industrial and motor vehicle accidents [16,20]. Studies have demonstrated that cognitive performance varies throughout the day [43], likely influencing the quality of our efforts and engagements-including how we use and interact with vehicles, devices, resources, * Research done during an internship at Microsoft Research.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep loss, in turn, impairs academic performance and also elevates risks of obesity, depression, and drug abuse. The biological mechanisms through which early starts increase health risks and lower performance are well-established (Carrell et al, 2011; Kirkby et al, 2011; Kelley et al, 2015). …”
Section: Introductionmentioning
confidence: 99%